Factors Affecting Breast Milk Substitute in Pidie Jaya, Aceh, Indonesia - Fazira, Frisca; Arisanti, Nita; Gurnida, Dida; Susiarno, Hadi; Azis, Muhammad Alamsyah; Rusmil, Kusnandi (Althea Medical Journal, 2024)
Background: Breast milk is the first, main, and best natural food for babies. Breast milk contains various nutrients needed in the process of growth and development of babies. Breastfeeding is a health behavior carried out by mothers. This study aimed to analyze the factors that influence the provision of breast milk substitutes.Methods: This was a quantitative study, using a cross-sectional design. Data collection was carried out from July to August 2022 on 71 mothers who had babies aged up to 6 months at the Bandar Baru Public Health Center, Pidie Jaya, Aceh, Indonesia. Consecutive sampling technique was used. The variables studied included behavior intentions, social support, accessibility of information, personal autonomy, and situational action. Chi-square was used to assess the relationship between independent variables and the dependent variables.Results: Most mothers were aged 20–35 years (70.4%), had junior high school education (78.9%), were unemployed (76.1%), and most did not provide breast milk substitutes (70.4%). Mothers who provided breast milk substitutes was significantly associated with the mother’s intention to give breast milk (p=0.002) and environmental conditions/situations for action (p=0.001). Mothers with low intentions tended to substitute breastmilk (53.8%). Furthermore, the situation of action influenced mothers to provide breast milk substitutes (48.6%).Conclusion: Factors that influence mothers to provide breast milk substitutes are low intention and environmental conditions/situations to act. Therefore, education for mothers to give exclusive breast milk is encouraged.